2015
DOI: 10.1590/1415-52732015000500003
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças entre sexos nos determinantes da obesidade abdominal em adultos de 40 anos ou mais: estudo de base populacional

Abstract: Objetivo:Verificar diferenças entre sexos na prevalência de excesso de peso abdominal e seus determinantes em adultos a partir de 40 anos de idade.Métodos:Estudo transversal de base populacional realizado no município de Cambé, Paraná, com 1.161 indivíduos de 40 anos de idade ou mais, residentes em todos os setores censitários urbanos. A obesidade abdominal foi definida como circunferência da cintura ≥88 cm para mulheres e ≥102 cm para homens. A análise de fatores associados foi realizada para cada sexo por me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 16 publications
1
8
0
12
Order By: Relevance
“…In a study conducted in Brazil, 83.7% of the 369 individuals had inappropriate WHR values and 85.4% were women and 89.7% were sedentary, 21 a fact that agrees with our findings. A study in our region showed prevalence of abdominal obesity for 49.7% in men and women, and was higher in women (more than double that in men) and increases with age progression, mainly from 50-year old, 20 being similar to our results that there was prevalence in all ages with higher emphasis from 40 to 59 years. Other research reports that there are greater risks for cardiovascular events with increased waist circumference, 22 indicating that women from our study have risk for developing chronic diseases, because they have high values on the WHR, BMI and body fat percentage, followed by high obesity rate.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In a study conducted in Brazil, 83.7% of the 369 individuals had inappropriate WHR values and 85.4% were women and 89.7% were sedentary, 21 a fact that agrees with our findings. A study in our region showed prevalence of abdominal obesity for 49.7% in men and women, and was higher in women (more than double that in men) and increases with age progression, mainly from 50-year old, 20 being similar to our results that there was prevalence in all ages with higher emphasis from 40 to 59 years. Other research reports that there are greater risks for cardiovascular events with increased waist circumference, 22 indicating that women from our study have risk for developing chronic diseases, because they have high values on the WHR, BMI and body fat percentage, followed by high obesity rate.…”
supporting
confidence: 91%
“…Our sample was small not representing the southern region of the country, which have values greater than the national average, as shown in another study done in our region with men and women over 40-year old, showed 12.1% of individuals that reported having Diabetes, which differ from our findings. 20 In anthropometric measurements in our study, the WHR was elevated in 91.6% of women. In a study conducted in Brazil, 83.7% of the 369 individuals had inappropriate WHR values and 85.4% were women and 89.7% were sedentary, 21 a fact that agrees with our findings.…”
mentioning
confidence: 42%
“…This can be explained by the use of different measuring methodologies among the studies, in addition to possible sociodemographic differences in each country 9,13,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In old age, they may be associated with various losses, such as limiting access to activities that promote satisfaction and well-being, in addition to an increased risk of the onset and worsening of chronic diseases. A sedentary lifestyle, obesity, and lifestyle habits detrimental to health are risk factors for this population 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…(2) O excesso de adiposidade na parede abdominal e na região das vísceras provoca o aumento da "razão cintura-quadril", este pode levar a um prognós-tico de risco para a saúde, quando a circunferência da cintura exceder noventa e quatro centímetros em indivíduos do sexo masculino e oitenta centí-metros em indivíduos do sexo feminino. (3) A fisioterapia dermato-Funcional é uma área da fisioterapia que vem desmistificando os tratamentos estéticos, uma vez que atua na comprovação científica dos métodos e técnicas utilizadas para o tratamento da adiposidade abdominal como a ultracavitação, o ultrassom, a radiofrequência e a eletrolipólise. (4,5) A eletrolipólise é uma técnica destinada ao tratamento das adiposidades e acúmulo de ácidos graxos localizados.…”
Section: Introductionunclassified